The effects of early childhood intervention on child development and early skill formation. Evidence from a randomized experiment. - Malte Sandner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper presents results from a randomized evaluation of a home visiting program for disadvantaged first time mothers and their families implemented in three German federal states. At the end of the first year of the program, children in home visited families perform significantly better than those in the control families by 0.18 standard deviations in the Mental Developmental Index. Examination of gender differences revealed that home visited girls scored 0.30 standard deviations higher than girls in the control families, whereas boys scored similar in both groups. Results indicate no differences in the scores of the Psychomotor Developmental Index and the birth outcomes, despite 0.28 standard deviations higher birth weight for boys in the home visited families compared to boys in the control families. We find evidence for skill self productivity but in different magnitude for boys and girls. Furthermore, we analyze possible monetary returns of the program.
Keywords: J13; J12; I21; 330